Tinjauan Hukum Islam Terhadap Pelaksanaan Akad Al- MuḌᾹrabah Al-MuṬlaqah Dalam Produk Penghimpunan Dana BMT Amanah Ummah Gumpang Kartasura Sukoharjo - Sumiati, Sumiati, M. Muhtarom, SH, MH (2016)
BMT this forms one of produck from the private entrepreneur to support course of economy in Indonesia. Kinds of BMT product were produced must in accordance of MUI and must be consult by Dewan Syariah Nasional (DSN). BMT Amanah Ummah this also forms one of the Syariah Economi Enterprise that be located in Kartasura. BMT do the operasional have kinds of produck. Funding produck that use the special of contract. That is the Muḍārabah Al-Muṭlaqah contract. This contrack ease BMT to expand the money and ease to operasional of money for the rightful effort. Because this contract is not bound by owner of donation.The writer collect data use the interview way and documentasi way, data thet was gotten than processing by the deskriptif-analitic method. This method to description than analyze data that have gotten. This research use the field research method. In this research method the writer do the research at the object (BMT Amanah Ummah) to know realization of Muḍārabah Al-Muṭlaqah contrack.Based of research that done by writer, the writer concluded that realization of the Muḍārabah Al-Muṭlaqah contract appropriate for the Syariah Islam, there is not money lending but use the profit sharing that has agreed by both side thet relevant. And BMT requires to the customer to fill the declaration. In the declaration there are determinates like addendum of agreement and the customer must be legal codition